Cattle herd structure and herd dynamics in Gaushalas of Haryana - Yadav , Dinesh Kumar; Vij , Pradeep Kumar (Journal of Livestock Biodiversity, 2025)
This paper describes cattle herd structure and herd dynamics from a data set of 105 Gaushalas selected from Haryana state based on certain criteria. These Gaushalas, an important source of indigenous germplasm, were maintaining more than 96000 heads of cattle. Hariana, being the native breed of this area, is the predominant breed in these Gaushalas constituting about 71 % of the total cattle followed by crossbreds (23%). Herd structure of these Gaushalas indicated that majority of the animals (>72%) were of more than 3 years of age. Females constituted more than 82 % of the total cattle. Breeding bulls constituted only 17 % of the adult males. Majority of the adult females were dry (67 %) while only 6 % were in milk. The average inflow and out flow of cattle was 245 and 168 heads respectively. On an average, a Gaushala received about 153 animals from general public, 36 brought by the Gaushala management, 26 by district administration and 27 recovered by police (illegal transportation of animals). Gaushala management purchased very few animals (an average of 2 animals). Disposal of animals from these Gaushalas was very less. Majority was due to deaths (about 100 animals) followed by sale (49 animals) and donated to public (19 animals). The study will be helpful in identifying Gaushalas as conservation centre and formulating conservation strategies for improvement of cattle genetic resources of these Gaushalas, especially Hariana breed.